Neurotransplantation of magnetically labeled oligodendrocyte progenitors: Magnetic resonance tracking of cell migration and myelination - Bulte, J. W. M. (The National Academy of Sciences, 1999)
Demyelination is a common pathological finding in human neurological diseases and frequently persists as a result of failure of endogenous repair. Transplanted oligodendrocytes and their precursor cells can (re)myelinate axons, raising the possibility of therapeutic intervention. The migratory capacity of transplanted cells is of key importance in determining the extent of (re)myelination and can, at present, be evaluated only by using invasive and irreversible procedures. We have exploited the transferrin receptor as an efficient intracellular delivery device for magnetic nanoparticles, and transplanted tagged oligodendrocyte progenitor cells into the spinal cord of myelin-deficient rats. Cell migration could be easily detected by using three-dimensional magnetic resonance microscopy, with a close correlation between the areas of contrast enhancement and the achieved extent of myelination. The present results demonstrate that magnetic resonance tracking of transplanted oligodendrocyte progenitors is feasible; this technique has the potential to be easily extended to other neurotransplantation studies involving different precursor cell types.